Bile acid metabolism and FXR-mediated effects in human cholestatic liver disorders. (28th February 2022) - Molinaro, Antonio; Marschall, Hanns-Ulrich
Abstract : Intrahepatic cholestasis is the main feature of a group of liver diseases that are characterized by hepatic and systemic accumulation of bile acids due to impaired excretion of bile, based on inflammation of intrahepatic and extrahepatic bile ducts or dysfunction of hepatobiliary transport proteins. The nuclear bile acid sensor farnesoid X receptor (FXR) is central for the regulation of bile acid turnover, including synthesis, hepatic excretion and intestinal and hepatic uptake. Several drugs targeting FXR have been developed for the treatment of cholestatic liver diseases, and so far one of them has been granted conditional approval. In this review, we will discuss the current knowledge and the clinical and experimental data available on agents affecting FXR and bile acid turnover.